A case of giant benign localized fibrous tumor of the pleura - Uzunlar, Ali Kemal; Yaldiz, Mehmet; Özercan, Ibrahim H.; Yilmaz, Fahri; Balci, Akin E. (My University, 2000)
A 57-year-old man presented with progressively increasing shortness of breath. A chest roentgenogram showed the presence of a giant mass and magnetic resonance of the chest confirmed the mass with an inhomogeneous density in the right hemithorax. The patient underwent a thoracotomy. A tumor was seen to have arisen from the parietal pleura. Size of the tumor was 22×19×15 cm and weighed 2650 g. It was successfully resected. The pathological diagnosis of the tumor was giant benign localized fibrous tumor of the pleura.
Keywords: Benign mesothelioma; Pleural neoplasms